The Correlates of Developing Green Supply Chain Management Practices: Firms Level Analysis in Malaysia - Tulus Suryanto; Muhammad Haseeb; Nira Hariyatie Hartani (International Journal of Supply Chain Management, 2018)
Over all businesses are ever changing competition environment, organization are always required to make modification internally and externally to compete globally successfully into marketplace. Supply chain management is key sources for firms to gaining superior performance. The basic purpose of this paper is to examine the level of association between the two indicators management support and their organization learning with the concept of green supply chain management environment. Supply chain is globally increasingly important concerns for all business and challenge for them are logistics management. Total quality management (TQM) and environmental management come from firms experiences and procedure of organizational learnings. This study computed positive significant relationship with organizational learning mechanism; support of organization and GSCM practices adopted controlled variables from organizations size, regulations of country perspective, cost pressure by organization, practices of industry at different levels. Over all findings and implications of logistics management are discussed.